2021
DOI: 10.1038/s41598-021-89199-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the QT interval using the Apple Watch

Abstract: The inherited and acquired long QT is a risk marker for potential serious cardiac arrhythmias and sudden cardiac death. Smartwatches are becoming more popular and are increasingly used for monitoring human health. The present study aimed to assess the feasibility and reliability of evaluating the QT interval in lead I, lead II, and V2 lead using a commercially available Apple Watch. One hundred nineteen patients admitted to our Cardiology Division were studied. I, II, and V2 leads were obtained after recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…The multichannel smartwatch ECG reliably identified ST-segment changes in patients with acute coronary syndromes (NSTEMI and STEMI). Finally, we and others demonstrated that the smartwatches could be used in measuring the QT interval [ 8 , 9 ] and even Brugada syndrome [ 10 ]. As an additional feature, Apple developed the smartwatch Apple Watch 6 (Apple Inc, Cupertino, CA, USA) with a new sensor that consists of four LED clusters and four photodiodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multichannel smartwatch ECG reliably identified ST-segment changes in patients with acute coronary syndromes (NSTEMI and STEMI). Finally, we and others demonstrated that the smartwatches could be used in measuring the QT interval [ 8 , 9 ] and even Brugada syndrome [ 10 ]. As an additional feature, Apple developed the smartwatch Apple Watch 6 (Apple Inc, Cupertino, CA, USA) with a new sensor that consists of four LED clusters and four photodiodes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Apple Watch can reliably detect atrial fibrillation [ 4 , 5 , 6 ], and we previously showed the possibility of using this smartwatch to obtain multiple ECG leads [ 7 ] to detect ST-segment ECG changes. More recently, we and others demonstrated that it is possible to assess QTc measurements with the Apple Watch [ 8 , 9 ] and even Brugada syndrome ECG patterns [ 10 ]. Accordingly, the present study aimed to assess the feasibility and agreement of the Apple Watch 6 compared with a standard SpO 2 monitoring system to assess normal and pathological oxygen saturation in a large cohort of patients with cardiovascular disease, patients with lung disease and healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, might also be difficult for patients to record. (2) We found fair to good agreement between automated-SW-ECG QTc-measurements and manual 12-lead-QTc measurements. This SW-AI algorithm tends to underestimate the QTc interval which has also been reported with another device (3).…”
Section: Discussionmentioning
confidence: 52%
“…In southern California where this study was conducted, more than 66% of the population with a mobile device use an iOS product ( https://deviceatlas.com/blog/mobile-os-popularity-by-us-state ) allowing for more rapid adoption and a lower learning curve. Additionally, the Apple Watch provided the most accurate measure of heart rate [ 54 , 55 ], prioritized the privacy of users, and is lightweight.…”
Section: Methodsmentioning
confidence: 99%